2016
DOI: 10.1126/scitranslmed.aad3650
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal heparan sulfates promote amyloid pathology by modulating brain amyloid-β clearance and aggregation in Alzheimer’s disease

Abstract: Accumulation of amyloid-β (Aβ) peptide in the brain is the first critical step in the pathogenesis of Alzheimer’s disease (AD). Studies in humans suggest that Aβ clearance from the brain is frequently impaired in late-onset AD. Aβ accumulation leads to the formation of Aβ aggregates which injure synapses and contribute to eventual neurodegeneration. Cell surface heparan sulfates (HS), expressed on all cell types including neurons, have been implicated in several features in the pathogenesis of AD including its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
162
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(165 citation statements)
references
References 85 publications
(145 reference statements)
1
162
0
Order By: Relevance
“…1) (114-116). A recent study found that ablation of HSPG in postnatal forebrain neurons of APP/PS1 mice led to a reduction in both A oligomerization and the deposition of amyloid plaques (117). These reductions were driven by an accelerated rate of A clearance from the ISF.…”
Section: Apoe and A Clearancementioning
confidence: 99%
“…1) (114-116). A recent study found that ablation of HSPG in postnatal forebrain neurons of APP/PS1 mice led to a reduction in both A oligomerization and the deposition of amyloid plaques (117). These reductions were driven by an accelerated rate of A clearance from the ISF.…”
Section: Apoe and A Clearancementioning
confidence: 99%
“…Amyloid plaque formation plays a pivotal role in AD pathogenesis [38]. Accumulation of β-amyloid peptides (Aβ) in the brain is the first critical step in the pathogenesis of AD [39] and is mainly due to the aggregation of Aβ which is cleaved sequentially from amyloid precursor protein (APP) by two enzymes, β-secretase and γ-secretase. The order of cleavage is very important since if α-secretase cleaves APP first, then Aβ plaques are not formed.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Chabc treatment reduced the expression of Perlecan and CSPG and altered HA expression pattern (more dotlike). Then, the derived cortical spheroid outgrowth treated with A β 42 peptide together with different ECM-related biomolecules, including Heparin (Hep, compete with HSPG-A β binding), 48,49 HepIII, Chabc, and HA, were analyzed for cell viability (Figure 4). The treatment of cells with A β 42 together with Hep, HepIII, or HA promoted cell survival, indicated by the higher cell viability (Figure 4A,B).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the addition of heparin to the culture attenuates the effect of A β 42 on the cell viability, which might be due to the competition of heparin with the HSPGs for binding with A β 42 peptide. 48,49 …”
Section: Resultsmentioning
confidence: 99%